Effect of Low-Sodium versus Conventional Sodium Dialysate on Left Ventricular Mass in Home and Self-Care Satellite Facility Hemodialysis Patients: A Randomized Clinical Trial - Marshall, Mark R. (J Am Soc Nephrol, 2020)
BACKGROUND: Fluid overload in patients undergoing hemodialysis contributes to cardiovascular morbidity and mortality. There is a global trend to lower dialysate sodium with the goal of reducing fluid overload. METHODS: To investigate whether lower dialysate sodium during hemodialysis reduces left ventricular mass, we conducted a randomized trial in which patients received either low-sodium dialysate (135 mM) or conventional dialysate (140 mM) for 12 months. We included participants who were aged >18 years old, had a predialysis serum sodium ≥135 mM, and were receiving hemodialysis at home or a self-care satellite facility. Exclusion criteria included hemodialysis frequency >3.5 times per week and use of sodium profiling or hemodiafiltration. The main outcome was left ventricular mass index by cardiac magnetic resonance imaging. RESULTS: The 99 participants had a median age of 51 years old; 67 were men, 31 had diabetes mellitus, and 59 had left ventricular hypertrophy. Over 12 months of follow-up, relative to control, a dialysate sodium concentration of 135 mmol/L did not change the left ventricular mass index, despite significant reductions at 6 and 12 months in interdialytic weight gain, in extracellular fluid volume, and in plasma B-type natriuretic peptide concentration (ratio of intervention to control). The intervention increased intradialytic hypotension (odds ratio [OR], 7.5; 95% confidence interval [95% CI], 1.1 to 49.8 at 6 months and OR, 3.6; 95% CI, 0.5 to 28.8 at 12 months). Five participants in the intervention arm could not complete the trial because of hypotension. We found no effect on health-related quality of life measures, perceived thirst or xerostomia, or dietary sodium intake. CONCLUSIONS: Dialysate sodium of 135 mmol/L did not reduce left ventricular mass relative to control, despite improving fluid status. CLINICAL TRIAL REGISTRY NAME AND REGISTRATION NUMBER: The Australian New Zealand Clinical Trials Registry, ACTRN12611000975998.